Pengaruh Kompetensi Aparatur, Partisipasi Masyarakat, Dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Desa Di Kecamatn Jasinga Kab.Bogor - Isti Qodariah; Imar Halimah (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This research was conducted in villages in Jasinga District. The purpose of this study was to determine the effect of apparatus competence, community participation, and the use of information technology on the accountability of village fund management in Jasinga sub-district, Bogor district. This type of research is quantitative research. The data source used in this research is primary data. The population in this study were all villages in Jasinga District, Bogor Regency. The sample used in this study is using saturated samples, namely all villages with a total of 16 villages with a total of 64 respondents. Data collection was carried out using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results showed that the competence of the apparatus, community participation and the use of information technology had an effect on the accountability of village fund management.